2007
DOI: 10.1021/jp072637b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Mechanism of the NCO + HCNO Reaction

Abstract: The complex doublet potential surface of the NCO + HCNO reaction has been investigated at the QCISD(T)/6-311g(d,p)//UB3LYP/6-31G(d,p) level. We have found 29 isomers on the potential surface, which are connected by 38 transition states. The single-point energy calculations are performed at the high-level QCISD(T)/6-311G(d,p) for more accurate energy values. In various possible initial association ways, the end-N attack leading to HC2N2O2 a1 and a2 is the most favorable association way through a barrierless pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
1
20
1
Order By: Relevance
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 69%
“…Several experimental and computational studies on the kinetics of HCNO have been reported [16][17][18][19][20][21][22][23]. Despite the potential importance of O 3 , HNCO and HCNO we could not find neither experimental nor theoretical report on O 3 -HNCO or O 3 -HCNO interactions.…”
Section: Introductionmentioning
confidence: 69%
“…The structure and properties of HCNO such as vibrational frequencies, ionization energy, heat of formation, and so on have long been reported based on both experimental and theoretical methods. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The geometry of the HCNO has been determined by Beck et al [11][12][13] from the IR spectrum when they isolated HCNO for the first time in the pure state. Their results show that this acid has three bonds including H─C, C─N, and N─O in the molecule supporting the formyl nitrile oxide structure, HCNO, rather than the oxime structure, CNOH, 28 as proposed before.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reactions of HCNO with small radicals such as OH, NH (singlet and triplet), CN, and OCN were investigated either experimentally or theoretically. 3,[14][15][16][17][29][30][31][32][33][34] In general, theoretical results showed that the initial association to the C-atom in HCNO is a major entrance channel leading to the dominant products, and that this process can occur via either a barrierless process or a well-defined transition structure. For example, HCNO reacts with O( 3 P), CN, NCO in barrierless processes to form HC(X)NO, in which X is the reactant species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCNO is formed in combustion primarily by the CH 2 + NO [2][3][4][5] and HCCO + NO [6][7][8][9][10][11] reactions, and can be synthesized by vacuum pyrolysis of 3-phenyl-4-oximinoisoxazol-5(4H)-one [12][13][14]. Several experimental [15][16][17][18] and computational studies [19][20][21] on the kinetics of HCNO have been reported. There are many researchers have studied in this area, for example, Miller et al reported a theoretical study on the kinetics of the O+HCNO reaction [19]; Hershberger and coworkers reported an experimental study of the kinetics of O+ HCNO reaction, using diode laser infrared adsorption spectroscopy to detect the product species.…”
Section: Introduction Hmentioning
confidence: 99%